Clock‐controlled arylalkylamine N‐acetyltransferase (aaNAT) regulates circadian rhythms of locomotor activity in the American cockroach, Periplaneta americana, via melatonin/MT2‐like receptor. Issue 2 (24th June 2021) - Kamruzzaman, A. S. M.; Hiragaki, Susumu; Watari, Yasuhiko; Natsukawa, Takashi; Yasuhara, Akie; Ichihara, Naoyuki; Mohamed, Amr A.; Elgendy, Azza M.; Takeda, Makio
Abstract: Melatonin (MEL) orchestrates daily and seasonal rhythms (eg, locomotion, sleep/wake cycles, and migration among other rhythms) in diverse organisms. We investigated the effects of pharmacological doses (0.03‐1 mM) of exogenous MEL intake in the cockroach, Periplaneta americana, on locomotor activity. As per os MEL concentration increased, cockroach locomotor rhythm in light‐dark (LD) cycles became more synchronized. The ratio of night activity to 24‐h activity increased and the acrophase (peak) slightly advanced. MEL application also influenced total activity bouts in the free‐running rhythm. Since MEL slightly influenced τ in the free‐running rhythms, it is not a central element of the circadian pacemaker but must influence mutual coupling of multi‐oscillatory system components. Arylalkylamine N ‐acetyltransferase (aaNAT) regulates enzymatic production of MEL. aaNAT activities vary in circadian rhythms, and the immunoreactive aaNAT (aaNAT‐ir) is colocalized with the key clock proteins cycle (CYC)‐ir and pigment‐dispersing factor (PDF)‐ir These are elements of the central pacemaker and its output pathway as well as other circadian landmarks such as the anterior and posterior optic commissures (AOC and POC, respectively). It also partially shares immunohistochemical reactivity with PER‐ir and DBT‐ir neurons. We analyzed the role of Pamericana aaNAT1 ( PaaaNAT1 ) (AB106562.1) by injecting dsRNA aaNAT1 . qPCR showed a decrease in accumulations of mRNAs encoding PaaaNAT1. The injections led to arrhythmicity in LD cycles and the arrhythmicity persisted in constant dark (DD). Continuous administration of MEL resynchronized the rhythm after arrhythmicity was induced by dsRNA aaNAT1 injection, suggesting that PaaaNAT is the key regulator of the circadian system in the cockroach via MEL production. PaaaNAT1 contains putative E−box regions which may explain its tight circadian control. The receptor that mediates MEL function is most likely similar to the mammalian MT2, because injecting the competitive MT2 antagonist luzindole blocked MEL function, and MEL injection after luzindole treatment restored MT function. Human MT2‐ir was localized in the circadian neurons in the cockroach brain and subesophageal ganglion. We infer that MEL and its synthesizing enzyme, aaNAT, constitute at least one circadian output pathway of locomotor activity either as a distinct route or in association with PDF system.